A combined phylogenetic and numerical taxonomic study of Matthiola montana and M. anchoniifolia (Brassicaceae) - Aygören Uluer Deni̇z; Özüdogru, Bariş (Phytotaxa, 2024)
Matthiola montana and M. anchoniifolia are endemic to Türkiye and can be distinguished from each other by morphological features including siliques, leaves, petals, and hairs. Although these two taxa have traditionally been treated as separate species in all taxeonomic accounts, field and herbarium studies together with findings in the literature suggest that they should be considered at the subspecies level at the very least due to transitions in the aforementioned characters. To test this hypothesis, we evaluated all available herbarium specimens and specimens from field collections, conducting numerical and phylogenetic analyses based on the ITS region of the nuclear DNA. Our analyses, including the unweighted pair group method with arithmetic mean (UPGMA) and principal coordinate analysis (PCoA) as well as phylogenetic methods, consistently indicated that the two species did not form separate clusters. Therefore, our careful examination of the material, along with morphological and phylogenetic analyses, strongly supports the conclusion that M. anchoniifolia is not distinct from M. montana and should be a synonym of the latter.